Management of Regular School Operational Assistance Funds - Susilawati, Hadining; Arafat, Yasir; Furkan, Nuril (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe the management of the regular school operational fund which is the only source of financing in SMP Negeri 01 Belitang. Regular school operational fund management at this school consists of Budget Planning, Budget Execution, Budget Evaluation and Accountability. The method used in this research is field research using qualitative analysis with a descriptive approach. In this study, the data sources were obtained from the principal, vice principal, and treasurer, laboratory assistant, librarian and committee. Data collection techniques and procedures in this study were observation, interviews, and documentation. In school financing management, the regular school operational fund budget planning at SMP Negeri 01 Belitang has been carried out by the manager according to the education financing standards and technical instructions contained in the school activity plan and budget which is synchronized with the school work plan. The implementation of the regular school operational fund budget from receipts and expenditures is recorded and reported in accordance with the technical guidelines for regular school operational fund, and SMP Negeri 01 Belitang has followed the guidelines listed in the regular school operational fund technical guidelines, the allocations of which have been arranged in the school activity plan and budget. Evaluation, accountability and supervision of the BOS fund budget are in accordance with school operational fund management standards, internally by the school operational fund manager for SMP Negeri 01 Belitang and externally by the district school operational fund Management Team, the inspectorate at the end of each stage and the Provincial Supreme Audit Agency.